Dental status, visits, and functional ability and dietary intake of elderly in Israel - L. Natapov; D. Kushnir; R. Goldsmith; R. Dichtiar; S. P. Zusman (BMC, 2018)
Abstract Background Epidemiological studies have shown deterioration in dental health accompanying the ageing process. Tooth loss increases with age. Chewing ability is closely correlated with number of natural teeth present: there is a threshold of 20-21 teeth, below which chewing ability declines. The government of Israel is currently considering adding dental treatment for elderly to the basket of services of the National Health Insurance Law. Information on the influence of elderly's dental health on nutrition and general health status can contribute to the decision making process. Methods Secondary analysis of data collected on a subsample (N = 1776) of the cross-sectional Mabat Zahav - National Health and Nutrition Survey of the Elderly was done. Intakes of energy, fiber, protein, fruits and vegetables, associations with dental visits, dentures presence and functional ability were analyzed. Linear regression adjusted for confounders was performed. Results Statistically significant differences in dietary intake of energy, fiber, protein and vegetables were found between elderly who visited a dentist in the last year and those who did not. Elderly who possessed dentures had lower dietary intakes than their dentate counterparts. Elderly with functional problems such as impaired chewing had worse dietary intakes than the others. This was so after controlling for education, degree of interest in the relationship between nutrition and health and reading the nutrition label. Conclusions The findings in our study suggest that those who visited a dentist in the last year, had natural teeth and no denture/s and reported no chewing problems had better dietary intake. The results emphasize the importance of maintaining adequate dental health, preserving natural teeth and regular dental visits in the elderly to assure adequate nutrient status in this age group.